PENINGKATAN KEDISIPLINAN SISWA SMK NEGERI 2 SOE MELALUI PENGEMBANGAN PRESENSI ONLINE TERHUBUNG SMS GATEWAY DAN WHATSAPP - Vera Rosalina Bulu; Diana Yani Fallo; Asti Yunita Benu (Institut Teknologi Dirgantara Adisutjipto, 2021)
Online Attendance list connected to whatsapp and SMS gateway will make teachers and parents to be easier in controlling student attendance quickly and accurately. This kind of attendance list is applied at SMK Negeri 2 Soe. This system aims to provide information related to the students attendance of SMK Negeri 2 Soe every day until the recap every month. The method used is the Rapid Application Development (RAD) method. Rapid Application Development (RAD) is a software development method with an object-oriented approach to system development. There are 3 stages in this community partnership program, namely the planning stage for the data retrieval related to the development of the system, the stage of system design including fingerprint recording and online attendance list program trials as well as the implementation stage where students use this fingerprint press on a shift according to before and after school hour.. The results obtained shows that students, teachers and parents can easily and quickly increase the students’attendance of SMK Negeri 2 Soe. The process of controlling student attendance is easier and it has an impact on the discipline of SMK Negeri 2 students which is increasing.